Personal Branding Pustakawan Di Dinas Kearsipan Dan Perpustakaan Halmahera Utara - Rejune Junita Lesnussa; Leidy Ellen Gonie; Oliviane Oroh (Jurnal Pendidikan Indonesia (JOUPI), 2023)
The purpose of this study is to better understand the personal branding strategies used by librarians at the North Halmahera Archives and Library Office to build a positive perception of their profession and the institutions where they work, as well as to increase library visits and reading literacy through personal branding displayed by librarians. The methodology used in this study is qualitative descriptive with qualitative design applied based on careful consideration and observation of the information in the data set. Purposive sampling was used as a method to gather information in this study, by collecting three informants equivalent to the context. The time frame for data collection of this study runs from April 6 to April 12, 2023. The results proved from the three informants, who implemented the Eight Aspects of Personal Branding Formation from Peter. Montoya is only one informant. Researchers matched the personal brands that informants displayed obtained from interviews and observations.